Formulation of Wonderful base pomegranate shampoo and evaluation of it - Bhagyashri Nehete; Darshana P. Patel; Khushal S. Patel; Yogesh B. Rokade; Hitendra S. Chaudhari; Rahul B. Lovhare; Sunil P. Pawer (Recent Trends in Cosmetics, 2024)
The current study objective was to create and assess a herbal shampoo using natural ingredients that prioritized both efficacy and safty. The extracts of pomegranate (the active ingredient), curry leaves, hibiscus leaves, Fenugreek seeds and reetha were combined in varying amounts to make the shampoo. As ancient times, people are used herbal shampoos, which are cosmetic preparations made with traditional ayurvedic herbs, to clean their hair, scalp, and to beautify and manage their hair. Herbal shampoos are utilized for more than just cleaning; they also add shine, keep hair manageable, and reduce oiliness. Visual evaluation, wetting time, pH, solid content assurance, surface tension, detergency, dirt dispersion, conditioning effectiveness, and foam stability were all assessed using a variety of physicochemical procedures. The herbal shampoo has been created to exhibit excellent cleaning, detergency, foam stability, low surface tension, optimal pH, and conditioning activities. Herbal shampoo has a light dirt dispersion and a foam height. The shampoo formulations were not only far less harmful than the chemical conditioning agents, but they also strengthened the hair development and significantly decreased the amount of hair lost when brushing. To preserve the scalp’s acidic layer, the shampoos’ pH was adjusted .It was discovered to be safer, more efficient, and cost-effective.
Keywords: Stability; cream shampoo; efficacy; pH; pomegranate